ANALISIS REALISASI PEMBANGKITAN DAYA LISTRIK TERHADAP TARGET TAHUNAN DI PEMBANGKIT LISTRIK TENAGA PANAS BUMI LAHENDONG UNIT 5 DAN 6 - Sutrisno Alex Hutauruk; Agung Sutrisno; Charles Punuhsingon (JURNAL POROS TEKNIK MESIN UNSRAT, 2019)
Performance indicator is a quantitative measure that describes the performance achievement of a company that is used as the basis for future performance improvements. This research is related to a study of Lahendong unit 5 and 6 power plant performance evaluations using the base of PJBL (Electricity Purchase Agreement) and RKAP (Corporate Work Plan and Budget) in 2018. From the results of data analysis it was found that the PJBL indicator did not reach agreed targets. Besides that, downtime due to unscheduled maintenance is also quite high. From the results of the analysis of the causal factors it is known that there are main factors that cause the achievement of the performance targets. Some proposals improve the realization of PJBL and reduce downtime because unscheduled maintenance was also presented in this study.Â Keywords: RKAP, PJBL, performance, PLTP 5 & 6 Lahendong.